Analysis of High School Students' Perceptions of Continuing Studies at State Universities - Sutirna Sutirna; Oktaviarini Yahya Ramadhanty; Sayyid Agil Rifqi Munawar; Aneu Pebriani (Green Publisher Indonesia, 2026)
This research aims to analyze high school students' perceptions of continuing their studies at state universities based on internal and external factors. This research employed a survey approach involving Grade XII students from public and private high schools in Karawang Regency. The research instrument consisted of a questionnaire with 40 statement items covering internal and external indicators, supported by interviews with selected respondents. Data were analyzed using descriptive percentage analysis to determine the level of students' interest and the influencing factors. The results of the study indicate that both internal and external factors fall into the